Dietary diversity is not associated with haematological status of pregnant women resident in rural areas of northern Ghana - Saaka, M.; Oladele, J.; Larbi, Asamoah; Hoeschle-Zeledon, Irmgard (Hindawi Limited, 2017)
Information regarding how dietary diversity is related to haematological status of the pregnant women in rural areas of Northern Ghana is limited. This study therefore evaluated maternal dietary intake and how it relates to the nutritional status of pregnant women belonging to different socioeconomic conditions in Northern Ghana. Methods. This study was cross-sectional in design involving 400 pregnant women. Midupper arm circumference (MUAC) and anaemia status were used to assess the nutritional status of pregnant women. Results. The mean dietary diversity score (DDS) of the study population from ten food groups was (95% CI: 4.08 to 4.37). Of the 400 women, 46.1% (95% CI: 40.0 to 52.2) met the new minimum dietary diversity for women (MDD-W). The mean haemoglobin concentration among the pregnant women studied was 10.1 g/dl ± 1.40 (95% CI: 9.8 to 10.3). The independent predictors of haemoglobin concentration were maternal educational attainment, gestational age, frequency of antenatal care (ANC) attendance, number of under-five children in the household, size of MUAC, and maternal height. Conclusions. Irrespective of the socioeconomic status, women minimum dietary diversity (MDD-W) was not associated with anaemia among pregnant women resident in the rural areas of Northern Ghana.